SPE Energy Resources Conference 2014
DOI: 10.2118/169942-ms
|View full text |Cite
|
Sign up to set email alerts
|

Using Polymer Alternating Gas to Maximize CO<sub>2</sub> Flooding Performance

Abstract: Carbon dioxide (CO 2 ) has been used commercially to recover oil from reservoirs by enhanced oil recovery (EOR) technologies for over 40 years. Currently, CO 2 flooding is the second most applied EOR processes in the world behind steamflooding. Water alternating gas (WAG) injection has been a popular method to control mobility and improve volumetric sweep efficiency for CO 2 flooding. The average improved recovery is about 9.7%, with a range of 6 to 20% for miscible WAG injection. Despite all the success of WA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Therefore, Surfactant (SAG) and Polymer Alternating Gas (PAG) combine the characteristics recently mentioned with the properties of surfactants and polymers, respectively [437]. This is the reason why these processes are also called chemically enhanced Water Alternating Gas methods [363,[438][439][440][441][442][443][444][445][446][447][448][449]. However, these are just recent developments, so it is considered that further research must be carried out in the laboratory as well as in field pilot tests to validate the results obtained so far.…”
Section: Chemical Eor Combined Techniquesmentioning
confidence: 99%
“…Therefore, Surfactant (SAG) and Polymer Alternating Gas (PAG) combine the characteristics recently mentioned with the properties of surfactants and polymers, respectively [437]. This is the reason why these processes are also called chemically enhanced Water Alternating Gas methods [363,[438][439][440][441][442][443][444][445][446][447][448][449]. However, these are just recent developments, so it is considered that further research must be carried out in the laboratory as well as in field pilot tests to validate the results obtained so far.…”
Section: Chemical Eor Combined Techniquesmentioning
confidence: 99%
“…Polymer was proposed to overcome the problems of gas breakthroughs and gravity segregation by using polymers. Polymer alternating gas (PAG), combines the elements of CO 2 flooding with polymer flooding to enhance the sweep efficiency especially in high permeable zones [12][13][14] Polymer gas alternating water (PGAW) has been experimented on Canadian heavy crude oil and the results were promising [15]. The study compared, four techniques of flooding, CO 2 immiscible flooding, WAG, polymer and PAG.…”
Section: Introductionmentioning
confidence: 99%
“…They used three different polymer concentration of 0.1 Ib/STB, 0.2 Ib/STB and 0.3 Ib/STB. The highest oil recovery factor (RF) for PAG was about 19.7%, the recovery improved up to 12% compared to WAG, however this result was obtained at polymer concentration of 0.2 Ib/STB [12]. In the second case study, they compared the effect of several flooding scenarios including CO 2 injection, WAG, polymer flooding and PAG.…”
Section: Introductionmentioning
confidence: 99%
“…Plugging gas channeling is a major preventive method to control CO 2 breakthrough. It has been widely demonstrated that methods based on gel, foam, , and water-alternating gas , can effectively inhibit CO 2 breakthrough. However, these conventional methods are limited in tight fractured oil reservoirs because of difficult injection, poor stability, and low strength, resulting in failure to effectively improve the swept volume of CO 2 .…”
Section: Introductionmentioning
confidence: 99%